Complementary responses of stream fish and benthic macroinvertebrate assemblages to environmental drivers in a shale-gas development area - Jennifer Lento; Michelle A. Gray; Allison J. Ferguson; R. Allen Curry (Canadian Science Publishing, 2020)
Shale-gas production could impact freshwater quality through contamination of the physical and chemical habitat (e.g., fracturing fluids, untreated or treated effluent) or development-related impacts. Despite environmental concerns, information is lacking to support biomonitoring as a diagnostic tool to assess impacts of shale-gas production. We characterized water quality and biota in areas of high shale gas potential (Early Carboniferous bedrock in New Brunswick, Canada) and surrounding geologic areas, and we assessed patterns in benthic macroinvertebrate (BMI) and fish assemblages. Early Carboniferous stations differed primarily based on water chemistry, and BMI were associated with a gradient in conductivity and temperature across geologic classes. Concordance analysis indicated similar classification of stations by both organism groups, though fish were more related to turbidity and nutrients. Concordance among fish and BMI was strongest at high conductivity, Early Carboniferous stations. These results suggest that geology plays a strong role in driving abiotic habitats and biotic communities of streams, even at small spatial scales. Furthermore, they suggest BMI and fish can provide complementary information for biomonitoring in shale-gas development areas, with BMI responding to increased ion concentrations from surface water contamination, and fish responding to changes in nutrients and turbidity resulting from development.